ANALISIS KONTEN ERSONAL BRANDING INFLUENCER MOBILE LEGENDS : BANG-BANG (MLBB) @JONATHANLIANDI PADA MEDIA TIKTOK - Indriana, Fety; Indriastuti, Yudiana (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
The aim of this research is to find out and analyze Jonathan Liandi's Personal Branding on the TikTok platform. The type of research used is descriptive qualitative because this research explores the phenomenon of Jonathan Liandi's Personal Branding formation on TikTok social media. Data will be obtained from content creator Jonathan Liandi in the form of background, use of TikTok social media and their perceptions of using TikTok social media for Personal Branding with Digital Discourse approach. The findings of this study are that Jonathan Liandi, a former pro player in Mobile Legends: Bang Bang, is known as a consistent content creator who has strong personal branding through a variety of witty and authentic content. He often uploads tutorial videos, game strategies and hilarious moments that build close relationships with his followers. As a family man, Jonathan displays his humorous side both in everyday life and in his career as a creator. His complete commitment and appreciation for fan support keeps him relevant and respected in the world of e-Sports. Tujuan penelitian ini adalah Untuk mengetahui dan menganalisis Personal Branding Jonathan Liandi dalam platform  TikTok. Jenis riset yang dipakai ialah deskriptif kualitatif karena penelitian ini mengeksplor fenomena pembentukan Personal Branding Jonathan Liandi di media sosial TikTok, akan didapat data dari konten kreator Jonathan Liandi berupa latar belakang, penggunaan sosial media Tiktok dan persepsi mereka dalam menggunakan sosial media Tiktok untuk Personal Branding dengan pendekatan Digital Discourse. Temuan studi ini ialah Jonathan Liandi, seorang mantan pro player Mobile Legends: Bang Bang, dikenal sebagai konten kreator yang konsisten dan memiliki personal branding kuat melalui variasi konten yang jenaka dan autentik. Ia sering mengunggah video tutorial, strategi permainan, hingga momen kocak yang membangun hubungan erat dengan pengikutnya. Sebagai seorang family man, Jonathan menampilkan sisi humorisnya baik dalam kehidupan sehari-hari maupun dalam kariernya sebagai kreator. Komitmen penuh dan penghargaan terhadap dukungan penggemar membuatnya tetap relevan dan dihormati di dunia e-Sports.